Impacto da exposição ocupacional aos agrotóxicos sobre os níveis de cortisol plasmáticos em mulheres portadoras de câncer de mama e seu significado clínico - Jumes, Jaqueline Janaina (2023)
Pesticides have been pointed out as hormone disruptors, and may significantly affect the prognosis of hormone-dependent diseases as breast cancer (BC). Here we investigated the impact of occupational exposure to pesticides on the systemic levels of cortisol in female rural workers diagnosed with BC. Occupational exposure was determined by conducting interviews with a standardized questionnaire. Aiming to investigated cortisol deregulation, plasma samples (112 exposed and 77 unexposed) were collected out of cortisol physiological peak (at afternoon) and analyzed by method of cortisol immunoassay chemiluminescent, with paramagnetic particles for the determination quantitative analysis of cortisol levels in serum and plasma, measured in a automated. The results were categorized according to patients’ clinicopathological and exposure data. Women with BC exposed presented higher levels of cortisol concerning the unexposed. Higher cortisol levels were detected in BC exposed women carrying more aggressive disease (triple-negative BC), as in those with tumors over 2 cm, having lymph nodal metastasis, and under high-risk for disease recurrence and death. These findings support that the chronic occupational exposure to pesticides significantly deregulated cortisol circulating levels and can affect disease prognosis for BC patients.